Licensing of γδT cells for professional antigen presentation: A new role for antibodies in regulation of antitumor immune responses - Anderson, John (Landes Bioscience, 2012)
Following activation, γδ T cells display many properties of lymphocytes from the innate immune system, yet how they mediate antigen presentation remains an open conundrum. In humans, circulating γδ T cells that express the Vγ9Vδ2 T-cell receptor become reversibly licensed for professional antigen presentation only upon interaction with a target cell opsonized with IgGs.